Assessment of Some 'Ber' (Ziziphus Mauritiana Lamk.) Cultivars for their Mineral Composition - Yamdagni, R; Dahiya, S S; Ahlawat, V P (Annals of Arid Zone, 2016)
Leaf samples of 20 'ber' (Ziziphus mauritiana Lamk) cultivars growing under Hisar conditions were analysed for their mineral composition. Nitrogen content was maxmum in 'Banarsi Karaka' and minimum in Â·Umran' 'Desi Alwar' contained maximum phosphorus Potassium content was maximum in cv. 'Sandhura Narnaul'. 'Ponda' and 'Mudia Murhara' contained maximum calcium, whereas cv. Jallandhari was found to be richest in magnesium. ZinC and iron content in the leaves of different cultivars under study varied from 8 to 48 ppm and 30 to 165 ppm respectively.